Correlation of Vital Signs and Depth of Sedation by Modified Observer's Assessment of Alertness and Sedation (MOAA/S) Scale in Bronchoscopy. Issue 1 (January 2022) - Pastis, Nicholas J.; Hill, Nathan T.; Yarmus, Lonny B.; Schippers, Frank; Imre, Mihaly; Sohngen, Wolfgang; Randall, Ostroff; Callahan, Sean P.; Silvestri, Gerard A.
Abstract : Background: With complex, lengthy bronchoscopies, there is a need for safe, effective sedation. Most bronchoscopists strive for moderate sedation, though often difficult without compromising vital signs. The Modified Observer's Assessment of Alertness and Sedation (MOAA/S) scale is a validated 6-point scale assessing responsiveness of patients coinciding with the American Society of Anesthesiologists (ASA) continuum of sedation. It is commonly used in studying bronchoscopic sedation, but depth of sedation by MOAA/S and correlation with vital signs and adverse events has not been determined. Methods: This study was a post hoc analysis of a prospective, double-blind, randomized trial evaluating the safety and efficacy of remimazolam. MOAA/S and corresponding vital signs were used to assess the effect of the level of sedation on vital signs and adverse events. Results: A total of 23, 341 MOAA/S scores from 431 patients were recorded. Older and higher ASA class patients spent more time in deeper sedation (MOAA/S 0 to 1) (6% vs. 2%, P =0.01). Oxygen saturation was equal in deep sedation (MOAA/S 0 to 1) (97±3%) compared with moderate sedation (96±3%) ( P =0.11). Mean systolic and diastolic blood pressures were significantly lower when comparing MOAA/S 0 to 1 to MOAA/S 5 (systolic blood pressure: 126±19 vs. 147±24 mm Hg, P <0.01; diastolic blood pressure: 68±14 vs. 84±15 mm Hg, P <0.01). There was a nonsignificant trend towards lower heart rate at deep versus moderate sedation (84±15 vs. 94±18 beats/min, P =0.07). Respiratory rate was also comparable with moderate and deep sedation (17±5 vs. 18±6 beats/min, P =0.94). Conclusion: There was no clinically meaningful correlation between vital signs and depth of sedation assessed by MOAA/S. Older and higher ASA class patients spend more time in deeper sedation. However, when in deep sedation, there was no difference in vital signs other than a slightly increased incidence of clinically insignificant hypotension.